Impact of Dark Triads of Personality and Rejection Sensitivity on Mental Well-Being among University Students - Batool, Iram; Ishaq, Ghulam; Batool, Huma; Sohail, Iram (Pakistan Journal of Humanities and Social Sciences, 2025)
This study examined the relationship between dark triad personality traits, rejection sensitivity, and mental well-being among university students. Using a correlational research design, data were collected from a sample of 100 university students (50 men, 50 women), aged 18 to 30 years (M = 21.23, SD = 1.84), from public and private universities in Lahore. Measures included the Short Dark Triad (SD3) scale, Rejection Sensitivity Questionnaire (RSQ), and Warwick-Edinburgh Mental Well-being Scale (WEMWBS). Pearson product-moment correlation, hierarchical regression, and independent samples t-test analyses were conducted. The results demonstrated a direct negative effect between both dark triad traits and rejection sensitivity on mental well-being, but a parallel positive connection between the variables. A hierarchical regression analysis confirmed that dark triad traits and rejection sensitivity serve as independent predictors of diminished mental well-being among students. The results of a statistical t-test indicated that male participants scored more points than female participants on all three assessment measures, including dark triad traits, rejection sensitivity, and mental well-being. The obtained findings provide critical knowledge for clinical psychologists who intervene with personality characteristics impairing university students' mental well-being.